2011
DOI: 10.1177/0363546511417567
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Septic Arthritis After Anterior Cruciate Ligament Reconstruction Among Professional Athletes

Abstract: Participation in professional sports and having a combined lateral tenodesis are risk factors for the development of infection after ACL reconstruction. We hypothesize that professional athletes may be part of a specific group of patients at higher risk of infection after ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 27 publications
6
103
0
3
Order By: Relevance
“…The postoperative rehabilitation program may have negatively influenced the results of Anderson et al [3] and Goertzen and Schulitz [15], which were based on immobilization with a brace and early restricted ROM. Despite the additional lateral knee incision required for the extraarticular procedure and some authors suggesting a higher infection rate with the combined procedure [39], this complication was similar in both treatment groups. Ultimately, reoperation rates for recurrent meniscal injuries were not different in the two intervention groups.…”
Section: Discussionmentioning
confidence: 73%
“…The postoperative rehabilitation program may have negatively influenced the results of Anderson et al [3] and Goertzen and Schulitz [15], which were based on immobilization with a brace and early restricted ROM. Despite the additional lateral knee incision required for the extraarticular procedure and some authors suggesting a higher infection rate with the combined procedure [39], this complication was similar in both treatment groups. Ultimately, reoperation rates for recurrent meniscal injuries were not different in the two intervention groups.…”
Section: Discussionmentioning
confidence: 73%
“…Post-arthroscopy septic arthritis runs a more indolent course and is often due to slowly growing bacteria (e.g., coagulasenegative staphylococci or anaerobes), two facts that explain the longer time to treatment [19,20]. Nevertheless, the management strategy is the same, with first-line arthroscopy for an evaluation of the joint, lavage, and synovectomy.…”
Section: Discussionmentioning
confidence: 99%
“…They ultimately observed different shortfalls in the surgical equipment decontamination and sterilisation process that ultimately led to the development of an infection-preventing pathway for patients and providers. Sonnery-Cottet et al [7] also presented a consecutive series with 1957 ACLRs with an infection rate of 0.61 %. Those authors observed that this rate increased to 5.7 % in a subgroup of professional athletes that included 88 patients.…”
Section: Prevalencementioning
confidence: 98%
“…aureus and CNS (S. epidermidis and other coagulasenegative species) are the most common bacteria found in most series [2,3,5,7,10,11,[14][15][16]. Additionally, different methicillin-resistant S. aureus or anaerobium microorganisms have also been cultured as the origin of such infections.…”
Section: Aetiopathologymentioning
confidence: 99%
See 1 more Smart Citation